political practices And its impact between Kant and Marx - Al-Sudani, Left Ahmed Youssef (The International and Political Journal, 2022)
Because of the political impact on reality, especially that we have dealt with two major schools that represent most of the products in the historical and scientific process, where the Marxist school represents reality, materialism and the sensual aspect, and since the world in the later periods I mean in the eras close to us as well as contemporary schools began to tend to the correctness of what schools go to Materialism and practicality being more accurate and giving in terms of results in reality, so now the whole world is calling for the importance of what the practice and the scientific side go to, because if we go back with simple excavations to the past, we will find the twentieth and twenty-first centuries. Through what we find from material schools that occupied the past two centuries, but we find there are simple schools such as Marbon, and others that only called for the spiritual direction, so researchers began to acknowledge and rely on what these schools go to in their material aspect in terms of using practice in order to reach the eligibility of the practical and scientific school